Vulnerability and physical well-being of caregivers: what relationship? - Salvatore Settineri; Fabio Frisone; Angela Alibrandi; Emanuele Maria Merlo (Journal of Mind and Medical Sciences)
Objectives. To assess relationships among burden, compassion, and well-being and health among an active group of caregivers. Methods. 301 caregivers with female prevalence (F = 61.1%, M = 38.9%) and ages between 18 and 84 years old (average = 38.72; SD 13.36) participated. Evaluation was carried using standardized instruments to assess: Burdens (CBI), dimensions related to Compassion and Burnout (ProQOL-5), State of Well-being (Who-5) and particular health-related domains (Emotional state, Physical health, Depressive Polarity, Dysphoric Polarity-SF-36). Correlational analyses and multivariate linear regressions were performed. Results. Positive correlations emerged between Burdens and Compassion Fatigue, Well-being and Satisfaction; inverse correlations emerged among Well-being and Burnout, Compassion Satisfaction and Emotional State, with the exception of Time Dependence. Multivariate linear regression indicated relations among Compassion Fatigue with Depression and Social Burden, Compassion Satisfaction with Depressive Polarity and Dysphoria and Burnout with Social Burden. Conclusions. Caregivers’ work presents various risks, with negative outcomes that need to be addressed for this group of professionals. These risks present a professional and human development opportunity.